4(5c-1)-2=18c+6

Simple and best practice solution for 4(5c-1)-2=18c+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(5c-1)-2=18c+6 equation:


Simplifying
4(5c + -1) + -2 = 18c + 6

Reorder the terms:
4(-1 + 5c) + -2 = 18c + 6
(-1 * 4 + 5c * 4) + -2 = 18c + 6
(-4 + 20c) + -2 = 18c + 6

Reorder the terms:
-4 + -2 + 20c = 18c + 6

Combine like terms: -4 + -2 = -6
-6 + 20c = 18c + 6

Reorder the terms:
-6 + 20c = 6 + 18c

Solving
-6 + 20c = 6 + 18c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-18c' to each side of the equation.
-6 + 20c + -18c = 6 + 18c + -18c

Combine like terms: 20c + -18c = 2c
-6 + 2c = 6 + 18c + -18c

Combine like terms: 18c + -18c = 0
-6 + 2c = 6 + 0
-6 + 2c = 6

Add '6' to each side of the equation.
-6 + 6 + 2c = 6 + 6

Combine like terms: -6 + 6 = 0
0 + 2c = 6 + 6
2c = 6 + 6

Combine like terms: 6 + 6 = 12
2c = 12

Divide each side by '2'.
c = 6

Simplifying
c = 6

See similar equations:

| 1=2a+b | | 2xy-y=10 | | C=24 | | 1/14(a-4)=2/7(a+6)-1/7a | | -24=-8x+48 | | 0=112-3x+2 | | 3y+2(y+1)=4 | | 5xy=5x+5y | | 52=x-7x-2 | | 7-10x=33-24x | | x+(3y+3z)= | | -3r-3r=5r+3 | | (5/4)-(3)/(6x+12)=(1/3) | | 25-8=-12 | | 7k^2-13=-9k | | x+b+23.34y=2b+3y+x | | 7x+50=3x | | 7(t-3)+4t=3(7+t) | | 8x+35=155 | | k/3=-11 | | x+y=4y+3-2x | | -13x+38=(-6x)-25 | | a(b-x)-b(2a-x)=6 | | a+b+c=9a-9b+9 | | 2a+3b+4c=9a-9b+9c | | 2.8d=2.1 | | x+y=4z-10 | | 3x+(10x-x)2.2= | | 2a+3b+4c=9abc | | 92-2x=10+20 | | -2p+10=-12p-20 | | B-5x=-3 |

Equations solver categories